The conflict in the Democratic Republic of Congo (DRC) and the persistance of the crisis in the Kivus - Mumwi, Simon Marco (My University, 2014)
This study sets out to examine the causes for the continued conflicts in the Kivu particularly after the establishment of a transitional government in the DRC in 2004 and the elections in 2006. Three factors appear to account for the continued conflicts. First is the ethnic divide between the local population and the Kinyarwanda speakers that have settled in the region overtime. This conflict is mostly centered on the land issues which were not addressed in the final agreements for the establishment of the transitional government in Kinshasa, at Sun City in 2002. It should not be surprising that this sparked new fighting in 2006 after the elections. Second is the continued existence of a central power vacuum. This is mainly because the national army is neither strong nor disciplined enough to establish its hegemony in the area. Its task was made more difficult by the continued Rwandan interests in the area, which went beyond security concerns. Thus the Nkunda rebellion was only successful because of Rwandan support. Third is the continuation of the war economy centered on the exploitation of natural resources that are abundant in the area. This has helped to fund the war in the Kivus, and as long as there are profits to be made from natural resources exploitation, conflicts and violence in the area will continue. The conclusion from this study is that peace in the Kivus needs the establishment of a central administration with both military power to secure the area, in particular the mining areas and judicial authority to prosecute the warlords and armed groups that continue to benefit from the continuation of conflicts and violence in the area.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2012.
Keywords: Politics and government; Violence; Democratic Republic of Congo